Rodion Raskol’nikov – “Strongman” between Two Women. Some reflections on Prestuplenie i nakazanie - Brodal, Jan (Poljarnyj vestnik, 2006)
This article reflects on the relationships between Rodion Raskol’nikov and the women that surround him in Dostoevskij’s Prestuplenie i nakazanie (Crime and Punishment).
Keywords: Russian; literature; Dostoevskij; Crime and punishment